Using MS Power BI visualization and dashboard to improve financial reporting in a data analytics company - De Guzman, Jose Arvin C. (Animo Repository, 2022)
This action research addressed the inefficiency and ineffectiveness of the current process in financial analysis and management reporting of a data analytics company, ABC Ventures, Inc. By using a data science application tool MS PowerBI, our Finance team was able to process and analyze financial and non-financial data from different sources and to prepare the management report in an efficient and effective manner. I, as the action researcher, collaborated with members from the Finance Team and with the Data Team and IT Team. We used the Business Intelligence framework in designing the flow of data from three different layers and sources of information. The agile methodology, particularly the Kanban system, assisted our team in implementing the process improvement. We also used DataPine Management Reporting as guide in creating an effective and informative dashboard and report. After conducting two action research cycles, the financial analysis and management reporting process significantly improved, reducing the number of man hours to complete the whole process. Our Finance team was able to provide financial reports to the management committee in reduced time and in a more effective manner.